Ameliorative Effects of Lutein Supplementation against Cardio-toxicity Induced by Ciprofloxacin and Daunorubicin: in Rats - Alaa R. Khudhair; Nada N. Al-Shawi; Mohammed Abdulameer Oleiwi; Israa Radhi Khudhair Khudhair (Iraqi Journal of Pharmaceutical Sciences)
A molecular mechanism of the ciprofloxacin adverse effects provoked thruogh the inhibition of the topoisomerase II in the mitochondrial that cause mitochondrial DNA impairment of transcription and replication. Daunorubicin (DNR) clinical use has been limited by its cardiotoxicity. Iron-mediated increase oxidative stress in cardiomyocytes is the main mechanism of the anthracycline cardiotoxicity. Elevated levels of circulating cardiac troponins are myocardial damage predictors. Troponin T and I are cardiac troponins, while troponin C specific to the skeletal muscle. Lutein is an oxygenated carotenoid that derived from the diet in all mammalians including humans. Lutein has anti-inflammatory effects, anti-genotoxic, improving cardiovascular diseases, reducing cancers risk, and improving cognitive functions. This study investigates the cardiotoxicity induced by ciprofloxacin in comparing to the cardiotoxicity of daunorubicin through the measurement of cardiac troponin I, interleukin 6, GSH peroxidase 4 and cleaved caspase-3 levels in heart tissues; and to explore the protective effects of lutein versus the ciprofloxacin and daunorubicin induce cardiotoxicity in the rat. Thirty (30) adult Sprague- Dawley rats of both sexes. Animals are divided to five (5) groups of six (6) rats each: Group Ӏ: given 10% dimethyl sulfoxide for 15 successive days. Group ӀӀ: received Daunorubicin 20 mg/kg for last 3 days with cumulative dose (60 mg/kg) by IP injection. Group III: given for the last 5 days 500 mg/kg ciprofloxacin orally. Group ӀV: received oral dose of lutein (24mg/kg) daily for 15 consecutive days, and Daunorubicin by intraperitoneal injection. Group V: given lutein (24mg/kg) orally daily for 15 days, then given ciprofloxacin oral dose for last 5 days. Cardiotoxicity induced by ciprofloxacin and daunorubicin, associated by increasing levels of cardiac troponin I, interleukin 6, GSH peroxidase 4 and cleaved caspase-3 levels in heart tissues. pretreated cardiotoxic rats with lutein (Group ӀV and Group V) was showed significant decline in the cardiac troponin I level, also reversed oxidative stress markers; rat Glutathione peroxidase 4 levels, to the control level. Suppression of the apoptotic and inflammatory markers, by measuring rat interleukin 6 levels and rat cleaved caspase-3 levels respectively, in heart tissues.